2019
DOI: 10.17765/2176-9168.2019v12n3p1043-1066
|View full text |Cite
|
Sign up to set email alerts
|

Variação Espacial E Temporal Da Biodisponibilidade De Metais Na Região Estuarina Do Complexo Estuarino-Lagunar De Iguape-Cananéia, Sudeste Do Brasil

Abstract: O Complexo Estuarino-Lagunar de Iguape-Cananéia (CELIC) apresenta condições ambientais distintas entre suas porções Norte e Sul e sofre com diferentes pressões antrópicas. Este estudo avaliou a variação espacial e temporal da biodisponibilidade dos metais Fe, Zn, Mn, Co, Cu, Cr, Cd, Pb and Ni, nos sedimentos em 8 pontos do CELIC em 2 períodos de 2013. A avaliação da biodisponibilidade dos metais deu-se através do método da extração simultânea de íons metálicos e sulfetos volatizados por acidificação (SEM/SVA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The main metals found in the liver of the S. guyanensis (ww) were Zn (37.7mg kg -1 ), Pb (1.94mg kg -1 ), Cu (14.18mg kg -1 ), Cd (0.07mg kg -1 ) and Cr (2.84mg kg -1 ); the concentrations of Pb were higher than those found in livers of Sotalia fluviatilis off the coast of Ceará, northeast Brazil (Monteiro-Neto et al, 2003), while the concentrations of Cd were low and comparable in both studies. According to Salgado (2015), Pb showed the highest mean values ever described for the species. Regarding Chelonia mydas, elevated levels of Cu and Ni were found in the liver, with average dry weight basis values of 39.9mg kg -1 and 0.28mg kg -1 , respectively.…”
Section: Speciesmentioning
confidence: 91%
See 1 more Smart Citation
“…The main metals found in the liver of the S. guyanensis (ww) were Zn (37.7mg kg -1 ), Pb (1.94mg kg -1 ), Cu (14.18mg kg -1 ), Cd (0.07mg kg -1 ) and Cr (2.84mg kg -1 ); the concentrations of Pb were higher than those found in livers of Sotalia fluviatilis off the coast of Ceará, northeast Brazil (Monteiro-Neto et al, 2003), while the concentrations of Cd were low and comparable in both studies. According to Salgado (2015), Pb showed the highest mean values ever described for the species. Regarding Chelonia mydas, elevated levels of Cu and Ni were found in the liver, with average dry weight basis values of 39.9mg kg -1 and 0.28mg kg -1 , respectively.…”
Section: Speciesmentioning
confidence: 91%
“…In addition to their presence in commercial species, metals were also found in Sotalia guyanensis cetaceans (Salgado, 2015) and Chelonia mydas turtles (Barbieri, 2009) from the CIEC. The main metals found in the liver of the S. guyanensis (ww) were Zn (37.7mg kg -1 ), Pb (1.94mg kg -1 ), Cu (14.18mg kg -1 ), Cd (0.07mg kg -1 ) and Cr (2.84mg kg -1 ); the concentrations of Pb were higher than those found in livers of Sotalia fluviatilis off the coast of Ceará, northeast Brazil (Monteiro-Neto et al, 2003), while the concentrations of Cd were low and comparable in both studies.…”
Section: Speciesmentioning
confidence: 99%
“…Frontiers in Earth Science frontiersin.org 16 Santos et al 10.3389/feart.2023.1142649 but the main source of Pb for the region is mainly from natural contribution, urban runoff, inadequate disposal of solid waste, and Pb present in aerosols resulting from the burning of fossil fuels. Pb can be correlated with suspended particulate material, which may favor the co-precipitation of Pb with Fe-Mn oxyhydroxides and PbCO 3 in an environment with pH > 6 (Nascimento, 2013;Paula Filho et al, 2014;Azevedo, 2019;Santos et al, 2019), explaining the large spatial distribution of Pb in these estuarine sediments. The anomalous concentrations of Pb reflect its bioaccumulation in oysters with values higher than the limits allowed by the Brazilian legislation ANVISA RDC n °42/13 (Ministério da Saúde.…”
Section: Organisms Of the Ezbn As Biomonitorsmentioning
confidence: 99%
“…Santos et al (2019) also found anomalous values for Mn in the same region, indicating the influence of ore shipment. Anil River and São José estuaries (MA), both located in the Maranhão Gulf, showed anomalous values, especially for Pb, resulting mainly from domestic and hospital sewage to the Anil River, while in the São José estuary, Pb was mostly derived from the lithogenic source with small anthropogenic contribution (Azevedo, 2019;Santos et al, 2019).…”
Section: Metals and Trace Metals In Estuarine Sediments Of The Ezbnmentioning
confidence: 99%
“…Pb is a toxic metal to aquatic biota and humans (Jesus and Cruz, 2019;Kütter et al, 2021), but the main source of Pb for the region is mainly from natural contribution, urban runoff, inadequate disposal of solid waste, and Pb present in aerosols resulting from the burning of fossil fuels. Pb can be correlated with suspended particulate material, which may favor the co-precipitation of Pb with Fe-Mn oxyhydroxides and PbCO 3 in an environment with pH > 6 (Nascimento, 2013;Paula Filho et al, 2014;Azevedo, 2019;Santos et al, 2019), explaining the large spatial distribution of Pb in these estuarine sediments. The anomalous concentrations of Pb reflect its bioaccumulation in oysters with values higher than the limits allowed by the Brazilian legislation ANVISA RDC n °42/13 (Ministério da Saúde.…”
Section: Assessment Of the Environmental Quality Of The Ezbn's Estuariesmentioning
confidence: 99%